Social Media Based EFL Learning: Opportunities and Challenges - Hisyam Nur Ahmad Latif (International Islamic Schools Alliance, 2021)
The growth of communication medium from traditional oral, as in face to face interaction, or written communication, as in letters, to the era of social media where people can communicate wirelessly without having to meet in person change the way people communicate with each other. Social media has become personal necessities for almost every person in order to communicate with their peers, acquaintance, friends, and families. It becomes unseparated part of human life. Thus, social media not only has affected people’s personal life, such as interacting with families, friends, and spouses for personal purposes but also their professional life. Mainstream social media platforms provide unlimited amount of information to language learning that change how human acquire information around them. This paper discusses the paradigm shift in education, the positive and negative effects of using social media as a language learning tool, and the conceptual framework in social media based teaching.